MicroRNA‐191, by promoting the EMT and increasing CSC‐like properties, is involved in neoplastic and metastatic properties of transformed human bronchial epithelial cells. Issue 1 (22nd September 2014) - Xu, Wenchao; Ji, Jie; Xu, Yuan; Liu, Yawei; Shi, Le; Liu, Yi; Lu, Xiaolin; Zhao, Yue; Luo, Fei; Wang, Bairu; Jiang, Rongrong; Zhang, Jianping; et al.
<x xml:space="preserve">Abstract</x> Lung cancer is the leading cause of cancer mortality worldwide. A common interest in lung cancer research is the identification of biomarkers for early diagnosis and accurate prognosis. There is increasing evidence that microRNAs (miRNAs) are involved in lung cancer. To explore new biomarkers of chemical exposure in risk assessment of chemical carcinogenesis and lung cancer, we analyzed miRNA expression profiles of human bronchial epithelial (HBE) cells malignantly transformed by arsenite. High‐throughput microarray analysis showed that 51 miRNAs were differentially expressed in transformed HBE cells relative to normal HBE cells. In particular, miR‐191 was up‐regulated in transformed cells. In HBE cells, arsenite induced increases of miR‐191 and WT1 levels, decreased BASP1 expression, and activated the Wnt/β‐catenin pathway, effects that were blocked by miR‐191 knockdown. In addition, a luciferase reporter assay indicated that BASP1 is a direct target of miR‐191. By inhibiting the expression of BASP1, miR‐191 increased the expression of WT1 to promote activation of Wnt/β‐catenin pathway. In transformed cells, inhibition of miR‐191 expression blocked the epithelial‐mesenchymal transition (EMT) and cancer stem cell (CSC)‐like properties of cells and decreased their migratory capacity and neoplastic properties. Thus, these results demonstrate that miR‐191 modulates the EMT and the CSC‐like properties of transformed cells and indicate that it is an onco‐miR involved in the neoplastic and metastatic properties of transformed cells. © 2014 Wiley Periodicals, Inc.